A escrita do aluno surdo: uma discussão acerca da interface entre a libras e a língua portuguesa - SILVA, Cleisiane de Vilhena (2019)
The present work was chosen from my observations of the education of the deaf realized during the practice of internship in a municipal institution of basic and infantile education of the municipality of Abaetetuba in the State of Pará, where we could perceive the variances that the writing of the deaf has in reference to Portuguese, the interlanguage call. The objective of this study was to analyze the educational process of the deaf in the context of the classroom. The central focus of the research is the interlanguage, that is, the influence of LIBRAS in the Portuguese Language writing of the deaf student. For the elaboration of this work, we adopted the methodology of qualitative bibliographical research, which served as a subsidy and foundations for this work. Among the main findings of this research is that inclusive education is a construct that needs to be consolidated and that LIBRAS as the mother tongue of deaf people has its characteristics and that modify the writing and perception of the latter, but that it becomes an efficient means of communication with the outside world. We believe that analyzing the issues surrounding the deaf culture is extremely important so that they can interact in the society in which they are inserted.